Analysis of Thermochemical Properties of three typical Manganese based thermite. Issue 2 (February 2020) - Zhu, Rui; Guo, Tao; Yao, Miao; Liu, Xiaofeng; Wang, Qiong; Ding, Wen
Abstract: In order to investigate the thermochemical and reactive properties of thermite composed of typical manganese oxides, three common manganese oxides meaning MnO2, Mn2 O3 and Mn3 O4, are selected in this paper to form aluminothermic agent with Al powder, respectively. According to the chemical thermodynamics, the difference of Gibbs free energy among different components is calculated, and the reaction rate k is calculated according to Eyring equation, then the Gibbs free energy values of three thermite at different ambient temperatures are drawn. Furthermore, according to the theory of chemical reaction calorific value calculation, the reaction calorific values of three thermite at different temperatures are calculated. The results show that the Gibbs free energy of Al/MnO2 system is the smallest at different temperatures, the reaction rate and the enthalpy of reaction of Al/MnO2 are the fastest and the smallest at different temperatures and the heat release is the largest. The results of calculation provide theoretical guidance for experimental design and practice. Under the condition of the same mass of reactants, the discharge heat of MnO2 is the largest, and the heat value of the MnO2 is the highest.